10 health questions about the new EU neig[h]bours - Arnaudova, Albena (WHO Regional Office for Europe, 2006)
This book offers a quick and easy way to grasp the essential features of health and health systems in the EU\'s neighbors. Each chapter provides a concise overview of key health indicators in 1 of the 12, comparing them to 3 averages for the EU: for its 25 current members the 15 members before May 2004 and the 10 new members. Each chapter also summarizes the key features of the country\'s health system and describes the results of more than a decade of health system reform.
Keywords: Cost Allocation; kohortové studie; řízení veřejného zdraví; poskytování zdravotní péče; Delivery of Health Care; veřejné zdravotnictví; Cohort Studies; Europe; ukazatele zdravotního stavu; Evropa; statistika přirozeného pohybu; alokace nákladů; Vital Statistics; Health Status Indicators; Public Health Administration; demografie